2021
DOI: 10.1002/elan.202100198
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐walled Carbon Nanotubes and Gold Nanorod Decorated Biosensor for Detection of microRNA‐126

Abstract: In this article, we introduced a novel electrochemical biosensor for the detection of microRNA‐126. The biosensor utilizes a hybridization assay combined with multi‐walled carbon nanotubes and gold nanorod‐decorated screen‐printed carbon electrodes. For electrode preparation, gold nanorods were first immobilized onto the surface of bare and multi‐walled carbon nanotube‐modified screen‐printed carbon electrodes, and the thiol tagged‐capture probe was immobilized on the electrode surface through gold and thiol g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The obtained high sensitivity is 12 times higher than the sensitivity of the bare carbon microchip loaded with LO x [7.118 μA/(mM cm 2 )] at the same amount of enzyme (0.625 U) (Figure S14). The limit of detection (LOD) was calculated to be 6.50 μM according to the formula LOD = 3σ/ S (where σ is the standard deviation of the blank sample and S is the slope of the regression curve) . Considering that the saliva was diluted to one-tenth of its original concentration in the buffer, the linear range for the salivary lactate was 0.1–3.7 mM, which satisfies the clinical requirement.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained high sensitivity is 12 times higher than the sensitivity of the bare carbon microchip loaded with LO x [7.118 μA/(mM cm 2 )] at the same amount of enzyme (0.625 U) (Figure S14). The limit of detection (LOD) was calculated to be 6.50 μM according to the formula LOD = 3σ/ S (where σ is the standard deviation of the blank sample and S is the slope of the regression curve) . Considering that the saliva was diluted to one-tenth of its original concentration in the buffer, the linear range for the salivary lactate was 0.1–3.7 mM, which satisfies the clinical requirement.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, CNTs exhibit good mechanical strength, excellent conductivity and remarkable electrocatalytic capacity [ 50 ], facilitating electron transfer for proteins or enzymes [ 51 ], and are unique due to the strong intermolecular bonds between the alternating hexagonal rings that lead to a crowded structure [ 52 ]. Moreover, recent publications have demonstrated that the modification of CNT electrodes facilitates electrochemical processes involving biomolecules and increases the measured signal [ 31 , 53 , 54 ]. On the other hand, GNP exhibit excellent electrical conductivity characteristics [ 55 ] (having unique chemical and physical properties, thus showing widespread use particularly for constructing electrochemical biosensors with a high electron transfer ability between the biomolecules and the electrode surface [ 56 , 57 , 58 , 59 ]), favorable biocompatibility [ 60 , 61 ], high specific surface area, which provides a stable immobilization of various biomolecules that thus retain their bioactivity [ 62 , 63 ], and, at the same time, a controllable particle size range, i.e., Jana et al prepared the AuNPs with diameters of 5–40 nm by varying the ratio of seed to gold salt [ 64 ], whereas Rodriguez-Fernandez et al prepared the AuNPs with diameters from 12 to 180 nm by incorporating small gold clusters on the surface of seed particles [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, CNTs exhibit good mechanical strength, excellent conductivity and remarkable electrocatalytic capacity [50], facilitating electron transfer for proteins or enzymes [51], and are unique due to the strong intermolecular bonds between the alternating hexagonal rings that lead to a crowded structure [52]. Moreover, recent publications have demonstrated that the modification of CNT electrodes facilitates electrochemical processes involving biomolecules and increases the measured signal [31,53,54]. On the other hand, GNP exhibit excellent electrical conductivity characteristics [55] (having unique chemical Previous studies containing theoretical calculations of the stability of the various catechin radicals have confirmed these trends: the 4′-phenoxyl radical was the most stable radical, and the other radicals were ordered in terms of their values characterizing electron affinity in the following sequence: 4′-OH, 3′-OH, 7-OH, 5-OH [49].…”
Section: Electrochemical Behavior Of Electrodes In Catechin Solutionmentioning
confidence: 99%
“…Topkaya and colleagues designed a special electrochemical bios sensor to measure miRNA‐126. The surface of SPCE was modified first with gold nanorods and then with multiwalled carbon nanotubes to measure the concentration of miRNA‐126 with a LOD of about 11 nM 72 …”
Section: Electrochemical‐based Biosensors For Mirna Detection In Ndsmentioning
confidence: 99%